Okuribito=departures : the gift of last memories - Nobukuni, Ichiro; Nakazawa, Toshiaki; Watarai, Toshihisa; Koyama, Kundo, 1964-; Takita, Yojiro, 1955-; Motoki, Masahiro, 1965-; Hirosue, Ryoko, 1980-; Yo, Kimiko, 1956-; Sugimoto, Tetta; Minegishi, Toru, 1943-2008; Yoshiyuki, Kazuko, 1935-; Sasano, Takashi, 1948-; et al. (OSCAR : classic movies, 2009)
Daigo Kobayashi, a cellist, dreamt of going around the world with his wife Mika. Unfortunately, the orchestra folds, so he sells his instrument, retreats to the small town he came from, lives in his late mother's house, and tries to start a new life. He answers a classified ad entitled 'Departures' thinking it is for a travel agency. Daigo's actual responsibilities entail preparing the local decedents for their "casketing," a process with an elaborate ritual of preparation, cleansing, and presentation, all done with great precision, grace, and utmost respect for both the deceased and watching family members. In dire financial straits, Daigo embarks on this new (and ancient) career path. While his wife and others despise the job, Daigo takes a certain pride in his work and begins to perfect the art, acting as a gentle gatekeeper between life and death, between the departed and their families.